As good as new – valuing fashion brands in the online second-hand markets. Issue 3 (16th May 2016) - Sihvonen, Jenniina; Turunen, Linda Lisa Maria
Abstract : Purpose: Brand management and marketing have focused on brand-new goods, thus largely neglecting the emergence of markets for used products. This study sheds light on how consumers determine the perceived value of fashion brands in online flea markets. In addition, this study aims to illustrate how fashion brands are perceived when sold second-hand in Facebook flea markets. Design/methodology/approach: Empirical data, consisting of internet discussions, were collected for this study from seven Facebook flea market forums between Fall 2014 and Fall 2015. The discussions were analyzed by means of qualitative content analysis. Findings: In the context of flea markets, the perceived value is negotiated and evaluated through six antecedents: perceived quality, price, design, origin, authenticity and brand availability. Not surprisingly, price and quality appear as focal aspects when determining the value of a used brand in second-hand markets. However, the aspects of availability, origin and design complicate the considerations of the perceived value and can distinguish between different flea markets for fashion brands. In online second-hand markets for fashion brands, the passing of time appears to be an important factor grounding the consumers' considerations of the perceived value. Originality/value: This study brings forward novel viewpoints to brand marketing by discussing the formation of the consumer-perceived value in the growing field of online second-hand sales of fashion brands.